Implementation of Vocational Skills for Students With Special Educational Needs in Primary Schools in Malaysia - Zulhafizsyam Zulkifli; Ardzulyna Anal (INCLUSIVE EDUCATION, 2023)
Vocational skills are important in career development and play an important role in the economic growth of a country. However, MBPK (MBPK) face major challenges in acquiring appropriate vocational skills, which affects their employability prospects. This study aims to investigate the implementation of vocational skills for MBPK in primary schools in Malaysia. The aim is to evaluate the effectiveness of the vocational skills program in improving MBPK employment outcomes. The methodological section describes the research design used in this study, including sampling techniques, data collection, and analysis. The research findings section presents the results of the study, highlighting the strengths and limitations of the vocational skills program. The discussion section analyzes and interprets the findings in the context of existing theory and research. Finally, the conclusion provides recommendations for the improvement of vocational skills programs for MBPK in primary schools in Malaysia, with an emphasis on the need to increase collaborative efforts between government agencies, schools and other stakeholders.